2022
DOI: 10.3390/ijerph192114402
|View full text |Cite
|
Sign up to set email alerts
|

Life-Course Persistent Antisocial Behavior and Accelerated Biological Aging in a Longitudinal Birth Cohort

Abstract: Prior research shows that individuals who have exhibited antisocial behavior are in poorer health than their same-aged peers. A major driver of poor health is aging itself, yet research has not investigated relationships between offending trajectories and biological aging. We tested the hypothesis that individuals following a life-course persistent (LCP) antisocial trajectory show accelerated aging in midlife. Trajectories of antisocial behavior from age 7 to 26 years were studied in the Dunedin Multidisciplin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 84 publications
0
1
0
Order By: Relevance
“…A subsequent follow-up study reported a significant increase in cardiovascular disease in individuals with lifelong severe trauma ( 43 ). Furthermore, middle-aged individuals with a history of antisocial behavior displayed an accelerated rate of biological aging ( 44 ), as shown in Supplementary Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A subsequent follow-up study reported a significant increase in cardiovascular disease in individuals with lifelong severe trauma ( 43 ). Furthermore, middle-aged individuals with a history of antisocial behavior displayed an accelerated rate of biological aging ( 44 ), as shown in Supplementary Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The factors influencing the risk of healthy aging mentioned earlier are not only relevant to specific stages of the life course, but they persist throughout the entire lifespan and impact the risk of healthy aging as well (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Among these, SES, educational level, and adversity are particularly influential, with SES's impact varying across variables like ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescent disruptive behavior is linked to serious negative long-term consequences and life outcomes for the youths themselves (Colman et al, 2009; Langevin et al, 2022) and to costs for society (Caspi et al, 2016). Although the importance of intervening during this crucial period is well known, treatments that have documented effects for adolescents exhibiting disruptive problem behavior are still in short supply (McCart et al, 2023).…”
Section: Study Objectives and Hypothesesmentioning
confidence: 99%